UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN PKN DENGAN PENDEKATAN KOOPERATIF MODEL NUMBERED HEADS TOGETHER ( NHT) DI KELAS V SD NEGERI 3 KERANGAN PURUN - Adi Adi; Muhammad Akip; Asep Eka Nugraha (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2021)
Abstract : This Classroom Action Research Aims To Know Improved Learning Outcomes in Civil Education Subjects Before And After Using The Numbered Heads Together (NHT) Cooperative Approach In Class V Elementary School Public 3 KeranganPurun. This research was conducted in two cycles, each cycle divided into 4 steps, consisting of planning, implementing actions, observing, and reflecting.Through This Research, Researchers Hope To Be Able To Improve Learning Outcomes In Pkn Subjects Before And After Using The Numbered Heads Together (NHT) Model Cooperative Approach In Class V Elementary School Public 3 PurunKerangan. Based on data analysis and discussion that has been done, that